2020
DOI: 10.1371/journal.pone.0240595
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and tuberculosis clinical presentation at the time of diagnosis in Puducherry and Tamil Nadu, India

Abstract: Setting Alcohol use increases the risk of tuberculosis (TB) disease and is associated with worse outcomes. Objective To determine whether alcohol use affects TB severity at diagnosis in a high-burden setting. Design Participants were smear-positive people living with TB (PLWTB) in India. Disease severity was assessed as 1) high versus low smear grade, 2) time to positivity (TTP) on liquid culture, 3) chest radiograph cavitation, and 4) percent lung affected. Alcohol use and being at-risk for alcohol use di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…However, the impact of alcohol use among TB patients, on their infectiousness and transmission to HHCs, is still not known [30]. Previously, we found that alcohol consumers had prominent chest X-ray findings compared to nonconsumers (adjusted mean difference 10.8%, p < 0.0001) but their alcohol use was not linked with mycobacterial burden, time to positivity, smear grade, or cavitation on chest X-ray [31]. In the current study, we hypothesised that TB patients who consume high bouts of alcohol would stay away from their home, thereby reducing the risk of exposure among their HHCs, but this was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 89%
“…However, the impact of alcohol use among TB patients, on their infectiousness and transmission to HHCs, is still not known [30]. Previously, we found that alcohol consumers had prominent chest X-ray findings compared to nonconsumers (adjusted mean difference 10.8%, p < 0.0001) but their alcohol use was not linked with mycobacterial burden, time to positivity, smear grade, or cavitation on chest X-ray [31]. In the current study, we hypothesised that TB patients who consume high bouts of alcohol would stay away from their home, thereby reducing the risk of exposure among their HHCs, but this was not found to be statistically significant.…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, family TB, cough 2 weeks, lost weight, contact cough 2 weeks, and alcohol showed insignificant correlations with MTB infection. A finding in sync as reported by Wijayamti [32], Gebrecherkos et al [33] and Melsew et al [34] but in contrast to Kan et al [35] , Jethan et al [36] and Reechaipichitkul et al [30]. This shows that these factors may not be reliable indicators of MTB infection.…”
Section: Discussionmentioning
confidence: 54%
“…Dependence on alcohol and tobacco is generally higher in men, which aggravates the initial clinical presentation at the time of TB diagnosis. Both alcohol abuse 20 and smoking 21 are associated with disease progression, disease severity, and poor treatment outcomes among patients with TB. Therefore, we aimed to adjust for these effects in multivariable analysis in order to exclude the potential influence of men's deleterious health behaviors.…”
Section: Discussionmentioning
confidence: 99%